Respostas

2013-12-13T15:20:11-02:00
A)  \frac{5x-3}{4} -  \frac{3x+8}{2} =  \frac{6x-3}{3} + \frac{x}{2}

Realizando o mmc dos denominadores -- > mmc = 12

3 . (5x - 3) - 6 (3x + 8) = 4 (6x - 3) + 6 (x)
15x - 9 - 18x - 48 = 24x - 12 + 6x
15x - 18x - 24x - 6x = -12 + 48 + 9
- 27x = 45

x =  \frac{45}{-27}

x =  \frac{5}{3}

b) \frac{x+3}{8} =  \frac{5}{4}

4. (x + 3) = 8 . 5
4x + 12 = 40
4x = 28

x =  \frac{28}{4}

x = 7
2013-12-13T15:23:00-02:00
1)
5x-3/4 - 3x+8/2 = 6x-3/3 + x/2        MMC de 4,2,3,2 = 12
15x-9/12 - 18x+48/12 = 24x-12/12 + 6x/12
15x-9 - 18x+48 = 24x-12+6x
15x -18x-24x-6x = -48 +9
15x-48x=-39
-33x=-39  (-1)
33x=39
x=39/33

2)
x+3/8 = 5/4         mmc de 8,4 = 8
x+3/8=10/8
x+3=10
x=10-3
x=7